Third Party Logistics Service Quality And The Moderating Role Of Switching Costs Between Customer Satisfaction And Behavioural Loyalty - Chin, Sze Hui (2014)
A multitude of companies has already identified the need to create a loyal customer base and acknowledged maintaining existing customers and extending businesses with them are significantly less expensive than acquiring new customers. Therefore this thesis describes the development of a conceptual model to investigate the factors affecting customer behavioural loyalty towards third party logistics (3PL) provider involving factors such as logistics service quality (LSQ), customer satisfaction and switching costs. One hundred and seventy four sets of completed questionnaire were collected from 3PL customers in the manufacturing sector from industrial hubs throughout Malaysia. Using Partial Least Squares - Structural Equation Modeling (PLS-SEM) analysis approach, the findings revealed four out of the nine dimensions of LSQ have positive relationships with customer satisfaction. The second order factor, functional quality and technical quality have positive relationships with customer satisfaction. LSQ as the third order factor has positive relationship towards customer satisfaction and behavioural loyalty. Customer satisfaction is a partial mediator in the relationship between LSQ and behavioural loyalty. Only procedural switching cost is a moderator towards the relationship between customer satisfaction and behavioural loyalty. Therefore, spurious loyalty is revealed in the relationship between customer satisfaction and behavioural loyalty when procedural switching cost exists. The findings of this study will help practitioners such as 3PL providers maintain close relationships with customers.